Intersectional Approach by Youth Feminist Activism “Girl Up” in Spreading Gender Equality Values in Southeast Asia (Indonesia, the Philippines, and Vietnam) - Lisa Angelina Putri Purnamasari*; Neneng Konety (Riwayat: Educational Journal of History and Humanities, 2023)
The feminist movement led by adolescent girls constitutes a new type of social movement striving for a revolution of anti-patriarchy society. This type of new social movement centers on instilling gender equality values at the grassroots level by promoting gender mainstreaming in every aspect of society. Guided by an intersectional feminist approach, Girl Up as a global initiative, adopts an inclusive approach that acknowledges the multifaceted struggles faced by girls, women, and marginalized communities with varying identities. This study seeks to elucidate the role of Girl Up in Southeast Asia, specifically in Indonesia, the Philippines, and Vietnam, in disseminating gender equality values through an intersectional feminist approach. The research draws upon the concepts of New Social Movement, Intersectional Feminism, and the "Girl Effect" and "Girl Power" discourses within International Development to uncover how Girl Up employs intersectional approaches in Southeast Asia to promote gender equality values within its domain. Using a qualitative descriptive methodology, the researcher combines literature analysis and interviews for data collection. The study reveals that Girl Up's feminist activism in Southeast Asia still concentrates predominantly on addressing local and national requisites and has yet to forge a robust regional network. Nonetheless, Girl Up effectively embraces an intersectional approach, thereby endorsing global frameworks and Sustainable Development Goals (SDGs) in its pursuit of gender equality.